2002
DOI: 10.1121/1.1428264
|View full text |Cite
|
Sign up to set email alerts
|

Effect of noise and occupancy on optimal reverberation times for speech intelligibility in classrooms

Abstract: The question of what is the optimal reverberation time for speech intelligibility in an occupied classroom has been studied recently in two different ways, with contradictory results. Experiments have been performed under various conditions of speech-signal to background-noise level difference and reverberation time, finding an optimal reverberation time of zero. Theoretical predictions of appropriate speech-intelligibility metrics, based on diffuse-field theory, found nonzero optimal reverberation times. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
56
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 8 publications
1
56
0
6
Order By: Relevance
“…Hodgson [10] carried out speech intelligibility tests by auralizing virtual sound fields to support the earlier work [9]. Although they were largely successful, they did not give the actual signal-to-noise ratios of their conditions and they made no attempt to confirm that their conditions would represent the balance between early-and late-arriving sounds that would commonly occur in real rooms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hodgson [10] carried out speech intelligibility tests by auralizing virtual sound fields to support the earlier work [9]. Although they were largely successful, they did not give the actual signal-to-noise ratios of their conditions and they made no attempt to confirm that their conditions would represent the balance between early-and late-arriving sounds that would commonly occur in real rooms.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has at other times been argued that increased reflected sound would increase both speech and noise levels and would result in no change to S/N values. Hodgson and Nosal [9] have explained that what is critical is the relative distances of the speech and noise sources from the listener. Their calculations, based on simple diffuse field theory, showed that when the noise source is closer to the listener than the talker, then added early reflections would usefully increase S/N values and hence would be expected to improve speech intelligibility.…”
Section: Introductionmentioning
confidence: 99%
“…Classroom quality was strongly correlated with the background noise level and the related signal-to-noise ratios (Hodgson, 2002), emphasising the need for the design criteria for occupied classrooms (Hodgson, Nosal, 2002). A number of studies (Hodgson et al, 1999;Sato, Bradley, 2008) have reported that the speech and noise levels are quite different from values measured in active classrooms with the influence of noise due to students' activity.…”
Section: Introductionmentioning
confidence: 99%
“…Noise is also affected by the reverberation time, as are the speech levels. Thus, the spatial relationship between a listener and the sound sources -both speech and noiseaffects the optimal reverberation for speech intelligibility in rooms [1].…”
Section: Introductionmentioning
confidence: 99%
“…Noise is also affected by the reverberation time, as are the speech levels. Thus, the spatial relationship between a listener and the sound sources -both speech and noiseaffects the optimal reverberation for speech intelligibility in rooms [1].In this project, an experimental approach to identify the optimal reverberation time in an idealized room, and validate theoretical prediction, considering babble noise sources inside the room, is presented using auralization. Realistic optimal reverberation times are found using speech-intelligibility tests with normal-hearing and hard-ofhearing subjects.…”
mentioning
confidence: 99%